Advances in and Applications of Microwave Photonics in Radar Systems: A Review - Luka Podbregar; Boštjan Batagelj; Aljaž Blatnik; Andrej Lavrič (Photonics, 2025)
Modern radar systems frequently encounter constraints on bandwidth, transmission speed, and resolution, particularly within complex electromagnetic settings. Microwave photonics (MWP) provides solutions through the integration of photonic elements to improve radar’s functionalities. This review paper examines the question of how to improve radar performance by using MWP-based radar components for signal transmission, local oscillator signal generation, radar waveforming, optical beamforming networks, mixing, filtering, co-site interference suppression, real-time Fourier transformation, and analog-to-digital conversion. MWP radar systems achieve wider bandwidths, greater resistance to electromagnetic interference, and reduced phase noise, size, weight, and power consumption. Consequently, the integration of MWP into radar systems has the potential to increase the accuracy of these systems.